Analysis of the GC-MS Volatile Compound Profile and Antibacterial Activity of 95% Ethanolic Extract of Siam Weed (Chromolaena odorata L.) Leaves from Kupang Regency Against Staphylococcus aureus - Saingo, Mathias Endrico; Regaletha, Tadeus A. L.; Purnasari, Cahyani; Kolobani, Matias Nataniel (Jurnal Biologi Tropis, 2026)
The need for new antibacterial medicines derived from natural sources is highlighted by the dangerous bacterium Staphylococcus aureus, which causes a variety of diseases and is increasingly linked to antibiotic resistance. The leaves of Chromolaena odorata (L.) contain a variety of bioactive compounds that may have antibacterial qualities. This study aimed to characterize the metabolite profile of the 95% ethanol extract of C. odorata leaves using gas chromatography–mass spectrometry (GC-MS) and evaluate its antibacterial activity against S. aureus. This true experimental post-test-only control group study was conducted from January to May 2026 using leaves collected from Mata Air Village, Kupang Tengah District, Kupang Regency, East Nusa Tenggara, Indonesia. Antibacterial assays were performed in four replicates using the disk diffusion method at extract concentrations of 5–25%. GC-MS identified 118 compounds, with ethyl palmitate, α-linolenic acid, phytol, stigmasterol, squalene, caryophyllene oxide, and α-muurolol as dominant metabolites that may contribute to the observed antibacterial activity based on previous studies. S. aureus was inhibited by the extract in a concentration-dependent manner; inhibition zones increased from 8.03 ± 0.04 mm (5%) to 11.41 ± 0.13 mm (25%), and there were significant differences between treatments (one-way ANOVA, p < 0.001). This study shows how GC-MS metabolite profiling and antibacterial assessment of the 95% ethanol extract of C. odorata can be combined in a unique way. These results suggest that the extract has antibacterial action against S. aureus and could be a source of natural antibacterial chemicals.